An auditing mechanism for the security of service in grid. (29th September 2014) - Liu, Zhusong; Li, Zhike; Sun, Sheng; Li, Yunfa; Mustafee, Navonil; Bessis, Nik; Barolli, Leonard; Chen, Xiaofeng; Xhafa, Fatos
Summary With the growth of system scale, ensuring the security of service in grid has become a challenge. To tackle this problem, an auditing mechanism for the security of service in grid is proposed in this paper. In the auditing mechanism, we first define and analyze some atomic services for grid application based on the service processes of tasks. Then, we propose several detecting methods for these automatic services. Finally, we propose an auditing model for the security of service and conduct a series of experiments to justify the availability and feasibility of the proposed auditing mechanism. The experimental results demonstrate that our approach is effective and efficient. Copyright © 2014 John Wiley & Sons, Ltd.